2010
DOI: 10.1007/s11764-010-0144-8
|View full text |Cite
|
Sign up to set email alerts
|

Pathologic femur fractures after limb-sparing treatment of soft-tissue sarcomas

Abstract: Survivors of soft tissue sarcomas of the femur may be at risk for the development of femur fractures and warrant close observation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 18 publications
1
33
0
3
Order By: Relevance
“…The overall rate of radiation-associated bone fracture in soft tissue sarcoma (STS) of the extremity is about 4-6%. [1][2][3] Most of these fractures occur in patients with lower extremity lesions, particularly the thigh. 4 Even within the thigh, there is a higher rate of fracture in anterior compartment tumors compared to medial or posterior compartments.…”
Section: Introductionmentioning
confidence: 99%
“…The overall rate of radiation-associated bone fracture in soft tissue sarcoma (STS) of the extremity is about 4-6%. [1][2][3] Most of these fractures occur in patients with lower extremity lesions, particularly the thigh. 4 Even within the thigh, there is a higher rate of fracture in anterior compartment tumors compared to medial or posterior compartments.…”
Section: Introductionmentioning
confidence: 99%
“…When the tumor lies adjacent to bone, some of the periosteum may be removed (stripped) in order to ensure adequate surgical margins. This combination of surgery and radiation greatly improves local control of these tumors,20–22 but several clinical studies have identified PS as a significant risk factor for post‐radiation pathologic fracture following surgery for extremity STS 20, 21, 23. In patients treated for STS of the thigh, PS is associated with an 18‐ to 20‐fold increase in the risk of pathologic femoral fracture, with the incidence of fracture at 5 years ranging from 29% to 32% 20, 21.…”
mentioning
confidence: 99%
“…In report by Blaes et al, post treatment pathologic fracture among soft-tissue sarcoma patients was identified to increase with time with overall incidence reported at 9% at 10 years 9 . In a study of gynecologic cancer patientes treated with radiation to the pelvis, the fracture incidence within the radiation field was 11% at 5 years and 15% at 10 years 3 .…”
Section: Discussionmentioning
confidence: 96%